Critical Synthesis Package: Collett-Lester Fear of Death Scale - Tziporah Rosenberg (Association of American Medical Colleges, 2013)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and the application to health science education of the Collett-Lester Fear of Death Scale (CL-FODS), and (2) a copy of the CL-FODS instrument and the scoring instructions developed by David Lester, PhD. The CL-FODS is a short, self-administered instrument with 28 items, divided into four subscales titled Death of Self, Death of Others, Dying of Self, and Dying of Others. The response options are presented along a 5-point Likert scale. Mean subscale scores and a total scale score can be calculated. Higher scores indicate more anxiety related to thoughts of death and dying. The scale has been developed and normed on groups of undergraduate students but has also been administered to populations of health professionals and learners such as nursing and medical students. The scale demonstrates concurrent and convergent validity with at least two other instruments used to assess attitudes about death. It has also been translated into several other languages and validated among native speakers of those languages. The most significant limitation has been the factor structure and the lack of studies that confirm a four-factor model.